Kinetic and kinematic patterns during high intensity clean movement: searching for optimal load - Ammar, A.; Riemann, B. L.; Masmoudi, L.; Blaumann, M.; Abdelkarim, O.; Hökelmann, A. (Journal of Sports Sciences, 2018)
The aim of the present study was to investigate loading effects on kinematic and kinetic variables among elite-weightlifters in order to identify an optimal training load to maximize power production for clean-movement. Nine elite-weightlifter (age: 24 ± 4years, body-mass: 77 ± 6.5kg, height: 176 ± 6.1cm and 1RM clean: 170 ± 5kg) performed 2 separate repetitions of the clean using 85, 90, 95% and 100%, in a randomized order, while standing on a force platform and being recorded using 3D-capture-system. Differences in kinematics (barbell displacement, velocity and acceleration) and kinetics (power, vertical ground reaction force (vGRF), rate of force development (RFD), and work) across the loads were statistically assessed. Results revealed significant load effects for the majority of the studied parameters (p < 0.01) and showed that typical bar-displacement, greatest bar-velocity and peak-power were achieved at 85 and 90% 1RM (p < 0.001). Additionally greater average power was shown for 90 and 95% (p < 0.01) and greater work and vGRF were shown for 90, 95 and 100% than 85% 1RM (p < 0.05). Load had no significant effect on peak-vGRF and peak-RFD (p > 0.05). The results of this study, suggest 90% 1RM to be the most advantageous load to train explosive-force and to enhance power-outputs while maintaining technical efficiency in elite-weightlifters.